2021
DOI: 10.26803/ijlter.20.11.2
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Self-Efficacy and Online Teaching during COVID-19 Pandemic in Qatari Governmental Schools

Abstract: This study investigated primary school teachers’ self-efficacy beliefs regarding online teaching during the Covid-19 pandemic and whether it determines any significant differences in self-efficacy levels based on different demographic data. A quantitative and qualitative survey method was employed. The data was collected from primary school teachers in Qatar public schools using a web-based survey that assessed self-efficacy in three areas: Students Engagement, Classroom Management, and Instructional Strategie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Second, the data related to socioeconomic and demographics of the inclusive school could be added to the study. Third, the experience of the teachers should be considered because several studies found that working experience acted as a significant factor for teachers' self-efficacy [12,9]. Finally, for future research, a mixed-method research design should be utilised to study self-efficacy further.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Second, the data related to socioeconomic and demographics of the inclusive school could be added to the study. Third, the experience of the teachers should be considered because several studies found that working experience acted as a significant factor for teachers' self-efficacy [12,9]. Finally, for future research, a mixed-method research design should be utilised to study self-efficacy further.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a study by [23] explained that substantial workload, In education settings, teachers had to collaborate not only with their colleagues but also with their student's parents and guardians. A study by [12] described one of the biggest obstacles for teachers to conduct effective online learning was uncooperative parents. If the parents are reluctant or refuse to be involved in their education, teachers would have trouble monitoring their students' learning process at home [3].…”
Section: Teacher's Self-efficacymentioning
confidence: 99%
See 2 more Smart Citations
“…In their teacher efficacy model, Tschannen-Moran et al (1998) indicate that teachers' self-efficacy is related to self-perception of competence. Therefore, assessment of teachers' self-efficacy should consider assessment of their competence (Allouh et al, 2021). This study investigated the lecturers' digital teaching competence and how it affected their self-efficacy in online classes.…”
Section: Introductionmentioning
confidence: 99%